Interaction of tannic acid with carbon nanotubes: enhancement of dispersibility and biocompatibility. Issue 1 (30th October 2014) - Zhang, Xiaoyong; Liu, Meiying; Zhang, Xiqi; Deng, Fengjie; Zhou, Cuiying; Hui, Junfeng; Liu, Wanyun; Wei, Yen
Graphical Abstract: Abstract: The interaction of manufactured nanomaterials with environmental and biological systems has been a subject of great research interest for a long time. In the present study, adsorption of a universal environmental organic material (named tannic acid (TA)) on carbon nanotubes (CNTs) was investigated. The influence of CNT properties and pH values on the sorption capacity of CNTs for TA was also evaluated. Our results demonstrated that the sorption capacity of CNTs was positively correlated with their specific surface areas. Furthermore, TA could effectively enhance the water dispersibility of CNTs and reduce their cytotoxicity. Our results implied that TA could influence the environmental behavior and biological responses of the manufactured nanomaterials, reminding us that much more attention should be paid to the synergistic toxicity of nanomaterials when we evaluate their environmental impacts.